PBL but not as we know it: an ethnography of the practice and facilitation of 'problem-based learning' within a hybrid graduate-entry medical programme in England - Jennings, Peter (2013)
This thesis lifts the lid' on the educational practices within a medical education programme, which is based upon a Problem-Based learning (PBl) approach. It is an ethnographic case study that sets out to understand the practice and facilitation of PBl situated within a hybrid curriculum at a graduate-entry medical programme in England. Data was collected by audio-visual recording of PBl sessions, audio recording and observing facilitator meetings and through the author's experiences as a participant observer working as a facilitator within the research setting. The study exposes a variety of PBl practices within a single curriculum setting that have not previously been examined in detail within medical education, in particular through use of direct observational methods. The findings pose a challenge to a core educational objective, upon which the 'PBl' programme was founded, that being to develop students' skills as self-directed learners. While this is highlighted within the literature as a central component to the PBl process, the findings raise questions about how these assumptions are reflected in the practice of PBL.